Perancangan Sistem Informasi Akademik (SIAKAD) Dengan Metode User Centered Design (UCD) Berbasis Website. Studi Kasus : PKBM Mutiara Ilmu - Dinar Aulia; Chairul Anwar (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2025)
In the comtemporary age of globalization era, the development of information technology has had a significant impact across various sectors, including education. Educational institutions have begun to integrate information technology to enhance operational efficiency, access to information, and the quality of academic services. However, PKBM Mutiara Ilmu, located in Purwosari District, Pasuruan Regency, still employs traditional methods such as manual recording and Microsoft Excel for academic and administrative data management, which are prone to recording errors and data loss. This study aims to design a web-based Academic Information System (SIAKAD) using the User Centered Design (UCD) method to replace traditional methods, integrate attendance management, daily assignments, and tuition fee payments, as well as improve security through the implementation of Cloudflare CAPTCHA during the login process. The design process involves requirements analysis, interface design, and testing with users as the central focus. The results show that the SIAKAD PKBM Mutiara Ilmu successfully accelerates the process of recording, searching, and managing data in a digital and integrated manner. Based on beta testing with 38 respondents, user satisfaction increased from 54.57% (fair category) to 97.76% (excellent category), with an increase of 43.19%. These findings demonstrate that the SIAKAD meets user needs, improves operational efficiency, and provides better data protection.